Aeolian Dust Provenance in Central East Antarctica During the Holocene: Environmental Constraints From Single-Grain Raman Spectroscopy - Paleari, Chiara Ileana; Delmonte, Barbara; Andò, Sergio; Garzanti, Eduardo; Petit, Jean Robert; Maggi, Valter (Geophysical Research Letters, 2019)
We analyzed the single-grain mineralogical composition of aeolian dust transported to central East Antarctica for provenance purposes. Comparison with data from the last glacial period shows for the first time disappearance of carbonates during the Holocene related to sea level rise and suppressed deflation from the Argentinean continental shelf, exposed during Marine Isotope Stage 2. Zeolites, related to alteration of volcanic glass in the subglacial/periglacial environment of Patagonia, show a similar behavior. The remaining minerals, remarkably similar between the two climatic periods, are compatible with a Pampean and Patagonian provenance, but Holocene data show a more pronounced volcanic and metamorphic imprint and presence of minerals related to warm climate weathering environments compatible with an additional contribution from subtropical latitudes of South America. These results do not imply a major large-scale reorganization of atmospheric circulation after the last climatic transition.